Analysis of the Residual Motion Error Impact on Airborne Multiband SAR Image Registration - Wu Qin-xia; Liang Xing-dong; Li Yan-lei; Zhou Liang-jiang (Leida xuebao, 2015)
Multiband SAR is an important trend in SAR technology. Accurate registration among different band SAR images is a prerequisite for the comprehensive utilization of the information of multiband SAR images. Errors in the motion measurement system (i.e., residual motion) are major error sources affecting image registration. To solve this problem, the effect of residual motion error on SAR imaging geometry positioning is investigated. The relation between residual motion and image registration accuracy of airborne multiband SAR is analyzed quantitatively. The results of the theoretical analysis are verified by simulation experiments.